INTRODUKSI TEKNOLOGI PENGOLAHAN TERUNG MENJADI MANISAN DAN DODOL SEBAGAI USAHA SKALA RUMAH TANGGA BAGI KELOMPOK IBU RUMAH TANGGA DI DESA TANJUNG SETEKO KECAMATAN INDRALAYA UTARA OGAN ILIR - Henny Malini (Lembaga Pengabdian pada Masyarakat, 2013)
Introduction processing technology eggplant into candy and lunkhead as household scale for the housewife inÂ Tanjung Seteko village indralaya sub distric Ogan Ilir Regency . This activities aim to 1 ) increase the value added through processing eggplant into candy and lunkhead as an alternative household enterprises that can contribute to the household income . 2 ) increasing the participation of women in the household in order to contribute to the economic needs of the household.Â in the Tanjung Seteko village many farmers who grow vegetables , one of the main types of vegetables is the most widely planted eggplant , but farmers only sold in fresh form so the price is cheap because there is no added value of these vegetables , such as eggplant cheap market prices , housewives are able to open opportunities is to cultivate a candied and lunkhead. The addition of this knowledge is very useful , it can also be a solution to increase the family income . With this knowledge in addition to make candied eggplant and eggplant lunkhead , mothers can also creation of own flavor and color of the candy and the purple eggplant lunkhead